ФРАЗЕОЛОГИЗМЫ КАК ЭТНОКУЛЬТУРОЛОГИЧЕСКИЙ ФАКТОР ДИАЛОГИЧЕСКОГО ОБЩЕНИЯ - Эминли, Б.И. (SCIENCE and SOCIETY, 2021)
This article includes materials of the research on ethnic cultural factors of dialogic communication. The aim of the research is to consider and analyze the language units which reflect nationality and culture of people in the process of speech communication. In the process of research we used descriptive and comparative descriptive methods, since the theory of dialog researches a lot of linguistic issues.
Keywords: cognitive linguistics; culture; national mentality; ethnic cultural characteristics; dialog; phraseological units